Bentuk Pergeseran Dialek pada Masyarakat Betawi - Riris Tiani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This research is related to sociolinguistic studies. The problem that emphasizes is the shift of the Betawi dialect in the family domain, especially the Betawi descendants who live in Jakarta. This study aims to determine the form of shifting Betawi dialect. Provision of data was taken using questionnaires and random interviews specifically aimed at some Betawi communities in the family domain. Then the data describe phenomenologically by looking at the basic principles of speech components as a reference for analysis. From the research that has been done, the results obtained that the dialect shift that occurs in Betawi occurs in the generation of children and parents, this form of shift can be identified in the use of shifting Betawi vocabulary into other vocabulary. Other languages are dominated by Indonesian, which indirectly is the second language of the Betawi community. While the causes of shifting dialects in the Betawi community include the influence of language variations and the lack of loyalty of the local community.